Safety of macitentan in sarcoidosis-associated pulmonary hypertension: a case-series - Mathijssen, Harold; Huitema, Marloes Petra; Bakker, Annelies; Snijder, Repke; Mager, Hans-Jurgen; Grutters, Jan; Post, Marco (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Pulmonary hypertension (PH) is a known complication of pulmonary sarcoidosis and is associated with higher morbidity and mortality. Currently, there are no approved PH-targeted therapies for sarcoidosis-associated pulmonary hypertension (SAPH). Macitentan is frequently used as treatment for pulmonary arterial hypertension, but no results are known in the SAPH population. Objective: We investigated the safety and effect of macitentan as treatment for SAPH. Methods: We retrospectively reviewed our patient database for all SAPH patients receiving macitentan as treatment, with a minimum follow-up of twelve months for monitoring safety. Safety outcomes included reported side-effects, hospitalisations and mortality. Furthermore, six-minutes walking distance, New York Heart Association functional class and NT-proBNP levels were collected. Results: Six cases (three men) with a median age of 64 years (range 52-74 years) were identified. During macitentan treatment, one patient experienced side effects and aborted therapy after five days of treatment and died 16 months later. Three patients were hospitalised during treatment for congestive heart failure. Four patients showed improvement of their functional class and three patients in exercise capacity after 12 months of therapy. Conclusion: Macitentan was well tolerated in five out of six cases with severe pulmonary sarcoidosis and PH. Functional capacity improved in four cases. Prospective controlled trials are warranted before therapeutic recommendations can be made.